Distribution Of Some Havey Metals In The Euphrates River Ecosystem Near Al- Nassiriya City Center South Iraq . - Al-khafaji, Basim; l-Khafaji, Basim (University of Thi-Qar Journal of Science, 2010)
The heavy metals Cd, Cu, Fe, Pb, and Zn were determined in dissolved and particulate phases of the water,in the exchangeable and residual phases of the sediment and in the selected organs of the fish Cyprinus carpio collected from the Euphrates River near Al-Nassiriya city center south of Iraq during the summer period / 2008 .Also sediment texture and total organic carbon(TOC) were measured. Analysis emploing a flam Atomic Absorption Spectrophotometers . The mean concentrations of the heavy metals in dissolved (µg/l) and particulate phases (µg/gm) dry weight were Cd (0.15,16.13) ,Cu (0.59,24.48) ,Fe (726,909.4) ,Pb (0.02, 49.95) and Zn (2.5,35.60) respectively,and those for exchangeable and residual phases of the Sediment were Cd (0.2,0.1) ,Cu (13.75,16.65) ,Fe (683 , 1351 ) ,Pb (10.1,1.07) and Zn (7.3,16.75)µg/gm dry weight respectively.The heavy metals consentrations in C. carpio organs followed the trend gill > liver > kidney> muscles . The mean concentration in the muscles were Cd (ND) , Cu (0.07) , Fe (4.7) , Pb(0.06) and Zn (6.4) (µg/gm) dry weight . The statistical analysis proved a significant correlation between metal concentration in the sediment and total organic carbon,also a positive correlation was proved between its concentrations in the liver organ and the water (particulate phase) . In conclusion the trace metals concentration in particulate phase were higher than its concentration in the dissolved phase . The fish organs showed variations in the metals concentration and the muscle organs showed less concentration than the other organs .